Daya Dukung Penerapan Green Infrastructure dalam Mendukung Kawasan Pertanian Lahan Berkelanjutan dan Agribisnis di Kabupaten Belitung Timur - Amo, Farisa Maulinam; Hidayah, Ulul (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
According to Peraturan Daerah (PERDA) Belitung Timur Regenc Number 4 of 2021, the regional government has prepared regulations regarding Sustainable Food Agricultural Land Protection (PLP2). This regulation was prepared as an effort to protect land quality to avoid land degradation, land conversion and increase agricultural production capacity in Belitung Regency. The aim of this research is to identify leading and promising commodities in East Belitung Regency as well as the supporting capacity for implementing green infrastructure that supports agricultural and agribusiness activities. The method used in this research is a mix method, namely to identify superior agricultural commodities in the East Belitung region and to analyze the level of performance of green infrastructure in the agricultural and agribusiness sectors in East Belitung Regency. The results of this research are that the management of agriculture and plantations managed by local communities in East Belitung Regency still faces many obstacles, including weak production and distribution, inadequate human resources to support the improvement of agriculture and agribusiness activities, and uneven provision of infrastructure to support development. sustainable agriculture. Gantung District, which is included in the PLP2B area, has experienced a decline in prospectivity in the five agribusiness sectors that are its basis due to the conversion of agricultural land to mining over the last four years. Based on the Importance-Performance Analysis (IPA) approach, the physical indicators, namely green streets and retention ponds, are in Quadrant III, meaning that in terms of availability they already exist in several locations which can be of benefit to the community even though they do not fully meet environmentally friendly aspects. Meanwhile, the indicator of improving physical and social well-being is an indicator that achieves low results, due to the resource capabilities of farmers.